Manutenção da certificação orgânica em produtores rurais - Scalco, Andrea Rossi [UNESP]; Servi, Renan Giovani [UNESP] (My University, 2014)
The regulation of organic compounds is a rather recent process and has experienced several changes since 1999, with three regulation landmarks in 1999, 2003 and 2007. Very strict laws for the production and the commercialization of organic products are extant. Law 10831 of 2003 and Decree 6323 of 2007 were the watershed for many producers of organic compounds, since the certification of their products became mandatory. Current analysis identifies the factors that contribute towards the loss of the certificate of organic compounds. Research employed the survey method with the sampling total referring to the ex-certificated producers of organic products in the state of Paraná, Brazil. Results show that impeding factors for the maintenance of the organic certificate are independent of the producers' control, or rather, they are factors related to the external environment such as public policies that trigger the sector and costs for the renewal of the certificate.
Maintenance of organic certification in rural products
Keywords: Certification; Organic produce; Organic products